Genotypic variation in Na, K and their ratio in 45 commercial cultivars of Indian tropical onion: A pressing need to reduce hypertension among the population - Singh, Hira; Lombardo, Mauro; Goyal, Abhishek; Kumar, Amrender; Khar, Anil (Frontiers in Nutrition, 2023)
The intake of diets with higher sodium (Na) and lower potassium (K) has been considered a leading factor for the development of hypertension (HTN). Majority of junk, processed and packaged food have higher Na contents. To counter the effects of diet on HTN, the identification of high K/Na ratio plant-based food is needed. Among fruits and vegetables, onion could be the ideal option since it contains high K content. Keeping this in mind, 45 commercially well adapted short day Indian onion cultivars were evaluated for K and Na content and their ratio to isolate suitable cultivars to prevent HTN in the Indian population. The data suggested wide variation among the genotypes for K, Na, and K/Na ratio ranging from 490.2 ± 17.0 to 9160.0 ± 96.7 mg/kg on dry matter basis, 52.7 ± 3.0 to 458.2 ± 61.7 mg/kg on dry matter basis and 3.1 ± 0.7 to 109.5 ± 17.3, respectively. The K content was recorded as significantly highest in the yellow-coloured bulb variety “Arka Pitamber” (9160.1 ± 96.7) followed by Pusa Sona (7933.2 ± 292.8). On the other hand, minimal K was assessed in the white-coloured bulb variety “Agrifound White” (490.3 ± 17.0) followed by Udaipur Local (732.9 ± 93.4). Twelve cultivars exhibited > 7000 mg K content, while nine cultivars recorded < 1500 mg. On the contrary, Na was recorded as significantly highest in the dark-red-coloured bulbs and the lowest in white bulbs. Furthermore, it was determined that there was a more than 35-fold difference observed between the highest (109.5) and lowest (3.1) K/Na ratio in the bulbs of tested cultivars. Cluster analysis revealed three major groups comprising of 23, 13 and 9 genotypes. This information could form the base for public health, food and onion researchers to design suitable cultivars to prevent HTN as a population-wide approach. The next century is going to be food-based for the amelioration of human diseases in a sustainable way without any after-effects on the human body.